EKSISTENSI PELAKSANAAN PERKAWINAN EKSOGAMI GAYO DI KABUPATEN ACEH TENGAH PROPINSI ACEH - ADITYA CAESAR (PREMISE LAW JURNAL, 2017)
ABSTRACT Every person has his own human right to get his offspring through marriage. The procedure of a marriage in Indonesia varies since Indonesia recognizes multi religions and ethnicities that have different procedures. The result of the research shows that the Gayonese community still perform exogamy marriage system with some reasons, and one of them is that they consider that one clan/belah is one offspring so that they will maintain this system forever. Since the majority of them are Moslems, a marriage will be valid when it has fulfilled rukun or requirements for a marriage. Even though it dooms to extinct, there is a unique procedure of the marriage system in the Gayonese community such as sesuk pantang, teniron, i sarahen ku guru, mujule mas, sedulung, nik mas, sawah ukun, upacara dalem, membilang mas, beru, and mah beru. If they do not use exogamy system, they will be imposed on an adat sanction like ‘farak’ (segregated) which is done by doing adat negotiation by sarak opai (adat institution). Keywords: Marriage, Exogamy, the Gayonese Community